Nutritional Status and Lung Cavity in Pulmonary Tuberculosis Patient - Hanafi, Christi Giovani Anggasta; Nurwidya, Fariz; Lestari, Wiji; Agustin, Heidy; Syam, Shaogi (Jurnal Respirasi, 2025)
Introduction: As one of the leading causes of death worldwide, pulmonary tuberculosis (PTB) is an infectious disease that continues to pose a serious threat to public health. The presence of cavities in radiological imaging of patients with PTB is associated with malnutrition, age, gender, and other comorbidities, including diabetes mellitus. This study aimed to find the association between nutritional status and lung cavity in PTB patients. Methods: This was an analytical observational study with a cross-sectional design that involved 134 adult patients who were diagnosed with PTB at Persahabatan National Respiratory Referral Hospital, Jakarta. All patients were interviewed using a questionnaire for sociodemographic and anthropometric data, the nutritional status was assessed using the subjective global assessment (SGA), and the lung cavity was determined using a chest X-ray interpreted by radiologists. The Chi-square test was performed using the Statistical Package for the Social Sciences (SPSS) version 25 for Windows. Results: Of 134 PTB patients, 61.9% were males, and 92.5% were from the 18-59 years old age group. Based on the SGA score, 77 (57.5%) were grouped as mild-moderate malnutrition/SGA B and 22 (16.4%) as severe malnutrition/SGA C. Lung cavity was found in 42 (31.3%) patients. The analysis showed that malnutrition was statistically significantly associated with lung cavity with OR=6.933 (95%CI 1.986-24.205; p=0.002) and the adjusted OR were 7.303 (95%CI 2.060-25.890; p=0.002) after controlling for age, sex, smoking, education, and comorbidities. Conclusion: This study found that malnutrition was associated with lung cavities in PTB patients. These findings might indicate how malnutrition impaired the immune function in PTB patients.